EVALUATION OF THE MACHINED SURFACE QUALITY OF SCOTS PINE (PINUS SYLVESTRIS L.) WOOD SPECIMENS, DEPENDING ON THE CUTTING MODE OF A CNC MACHINE - Doichinov, Aleksandar; Vitchev, Pavlin (Innovation in Woodworking Industry and Engineering design, 2024)
In this paper, the surface quality of scots pine (Pinus sylvestris L.) wood specimens, processed with a CNC woodworking drilling and milling machine with a negative face mill helix, has been investigated. The changes in the surface roughness, depending on the changes in main factors determining the cutting process, such as cutting tool rotation speed (n); feed speed (Vf) and radial depth of cut (h), have been evaluated. The quality of the processed surfaces was evaluated by the roughness parameter Rz, measured with a portable roughness tester, model Surftest SJ-210 (Mitutoyo, Japan).Based on the experiments performed, graphical dependencies, presenting the influence of the individual factors on the quality of the processed surface, were derived. A regression model was derived that could be used for quantitative prediction of the surface roughness of Scots pine wood specimens when processed with a CNC machine, depending on the changes of the variable factors (n, Vf, h).